ANALYSIS OF ACCURACY OF DETERMINING THE CENTRIC RELATION OF JAWS IN SECONDARY COMPLETE ADENTIA - Bayramov, Y.I. (World of Medicine and Biology, 2024)
The purpose of the study is to investigate the accuracy of determining jaw center relations in clinical practice in secondary complete adentia. In the study, complete removable plate prosthesis preparation was performed using the improved method in 204 patients aged 45 to 90 years, including 102 (50.0 %) men and 102 (50.0 %) women with secondary complete dentition, which constituted the main group. We performed traditional preparation of prosthesis in 405 patients aged 45 to 90 years, including 206 (50.9 %) men and 199 (49.1 %) women with second complete adenia, and formed a control group. The occlusal method was used to study the central jaw relationships in the central occlusal state. This method was compared with control group, when during preparing completely removed plate prosthesis, the area of the prosthesis and surrounding tissues are changed as a result of pressure when the doctor measures.
Keywords: secondary full adentia; central relation; central occlusion; orthopedic treatment; complete removable plate prosthesis; a state of relative calmness of the jaws; prosthetic bed